Alcohols as Alkylating Agents: Photoredox‐Catalyzed Conjugate Alkylation via In Situ Deoxygenation. (19th July 2022) - Wang, Johnny Z.; Sakai, Holt A.; MacMillan, David W. C.
Abstract: The rapid exploration of sp 3 ‐enriched chemical space is facilitated by fragment‐coupling technologies that utilize simple and abundant alkyl precursors, among which alcohols are a highly desirable, commercially accessible, and synthetically versatile class of substrate. Herein, we describe an operationally convenient, N ‐heterocyclic carbene (NHC)‐mediated deoxygenative Giese‐type addition of alcohol‐derived alkyl radicals to electron‐deficient alkenes under mild photocatalytic conditions. The fragment coupling accommodates a broad range of primary, secondary, and tertiary alcohol partners, as well as structurally varied Michael acceptors containing traditionally reactive sites, such as electrophilic or oxidizable moieties. We demonstrate the late‐stage diversification of densely functionalized molecular architectures, including drugs and biomolecules, and we further telescope our protocol with metallaphotoredox cross‐coupling for step‐economic access to sp 3 ‐rich complexity. Abstract : Alcohols are among the most commercially accessible alkyl fragments, yet their direct use in C(sp 3 )‐based fragment couplings remains underdeveloped. In this report, a mild strategy for the in situ activation of alcohols by benzoxazolium salts is applied to deoxygenative conjugate alkylation for a broad range of alcohol and Michael acceptor substrates, including structurally diverse drugs, natural products, and biomolecules.